Clinical outcomes of trabecular microbypass stent (iStent) implantation in medically controlled open-angle glaucoma in the Korean population. Issue 33 (14th August 2020) - Kim, Hee Jun; Lim, Su-Ho
Abstract : Abstract: To evaluate the safety and efficacy [intraocular pressure (IOP)-lowering effect and medication use] of a single trabecular microbypass stent (iStent; Glaukos Corp, San Clemente, CA) for medically controlled open-angle glaucoma. This retrospective case series included 42 eyes of 34 patients with medically controlled open-angle glaucoma with IOP less than 21 mm Hg. Clinical outcomes analyzed were IOP, medication use, corrected distance visual acuity (CDVA), and surgical complications. Surgical success was defined according to 4 criteria: IOP < 21 mm Hg without medication; IOP < 18 mm Hg without medication; IOP < 15 mm Hg without medications; and IOP < 18 mm Hg with or without medication. Patients were followed for a minimum of 6 months postoperatively. Mean IOP was reduced from 15.8 ± 2.8 mm Hg to 14.5 ± 2.8 mm Hg ( P  < .001), while mean number of medications decreased from 2.2 ± 1.2 to 0.8 ± 1.1 at final visit ( P  < .001). Surgical success rates were 78.6%, 61.9%, 57.1%, and 97.6% at 6 months and 78.6%, 59.5%, 52.4%, and 95.2% at final visits according to criteria A, B, C, and D. Meanwhile, 59.5% of patients were medication-free at their final visit. The relative risk of surgical failure by Criteria B and C was 4.337 (95% confidence interval: 1.799–10.454) and 3.717 (95% confidence interval: 1.516–9.116) times greater in the higher-medication group (3 or more preoperative medications), respectively. CDVA was significantly improved from 0.41 ± 0.10 to 0.09 ± 0.07 LogMAR in the combined phacoemulsification and iStent implantation group ( P  < .001). There was no case whose vision was threatened (vision loss of 2 or more lines) or who showed severe complications after surgery. Single trabecular microbypass stent implantation was effective in reducing IOP and medication usage in patients with open-angle glaucoma with a low preoperative IOP. Our results imply that it is more difficult to achieve low target IOP control in eyes with higher numbers of preoperative medications.